2021
DOI: 10.1002/cncr.33545
|View full text |Cite
|
Sign up to set email alerts
|

Training oncology care providers in the assessment and treatment of tobacco use and dependence

Abstract: BACKGROUND: Clinical practice guidelines for promoting smoking cessation in cancer care exist; however, most oncology settings have not established tobacco use assessment and treatment as standard care. Inadequate staff training and other implementation challenges have been identified as barriers for delivery of evidence-based tobacco treatment. Providing training in tobacco treatment tailored to the unique needs of tobacco-dependent patients with cancer is one strategy to improve adoption of best practices to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Indeed, tobacco training has been recognized as a driving force in changing health care providers’ knowledge and attitudes, heightening its benefit in any setting [ 39 ]. Moreover, unlike hard stops in the EHRs, training can happen in all health care settings, including those with paper patient records that preclude electronic hard stops, and is recommended to improve care delivery regardless of whether specific health care practices are mandated or not [ 34 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, tobacco training has been recognized as a driving force in changing health care providers’ knowledge and attitudes, heightening its benefit in any setting [ 39 ]. Moreover, unlike hard stops in the EHRs, training can happen in all health care settings, including those with paper patient records that preclude electronic hard stops, and is recommended to improve care delivery regardless of whether specific health care practices are mandated or not [ 34 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to understand the nature of CCP discomfort in addressing smoking, as well as knowledge deficits regarding the safety and effectiveness of tobacco treatment [ 11 , 15 ]. CCPs report inadequate training in tobacco use and dependence treatment [ 14 , 15 ] high-lighting the importance of increased education and training for smoking cessation in cancer care [ 22 ]. The Theme 1 finding strikes a cautionary note for CCPs who may have good intention for avoiding a potentially up-setting discussion about smoking but may not fully appreciate the deleterious effects of giving short shrift to cessation counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, these findings have contributed to the success of a tobacco treatment training workshop targeting CCPs and found that CCPs report increased post-training self-efficacy when discussing smoking with their patients. [ 22 ] The patient perspectives reported in this paper greatly advance the field by providing specific communication recommendations that CCPs can adopt to mitigate stigma and enhance lung cancer patients’ comfort, particularly when taking a routine smoking history.…”
Section: Discussionmentioning
confidence: 99%
“…A common refrain is that they are just too busy to address smoking cessation given the increasing complexity of the cancer care they are required to direct. In contrast, there is clear evidence that training oncology- care providers can have demonstrable impact on improving tobacco-treatment skills and tobacco-treatment delivery 97…”
Section: Cessation In Cancer Treatment Settingsmentioning
confidence: 97%
“…In contrast, there is clear evidence that training oncologycare providers can have demonstrable impact on improving tobacco-treatment skills and tobacco-treatment delivery. 97 If oncologists are to achieve the best clinical outcomes for their patients, the oncology centres in which they work must implement strategies to ensure that all newly diagnosed patients with cancer are screened for smoking status, advised of the benefits of smoking cessation and referred to smoking cessation services. An 'opt out' approach to the provision of smoking-cessation care can distinctly enhance the ability to ensure patients receive the supports required to optimise their cancer care.…”
Section: Cessation In Cancer Treatment Settingsmentioning
confidence: 99%